Bounds for the mean square error of reliability estimation from gamma distribution in presence of an outlier observation - M. E. Ghitany; W. H. Laverty (International Journal of Mathematics and Mathematical Sciences)
In this paper we discuss the behavlor of the statistic R^(t) , the uniformly minimum variance unbiased (UMVU) estimate for the reliability of gamma distribution with unknown scale parameter σ when an outlier observation is present. Given the outlier effect on σ, we determine bounds for the mean and mean square error (MSE) of R(t). A semi-Bayesian approach is discussed when the outlier effect on σ is treated as a random variable having a prior distribution of beta type. Results of the exponential distribution (Sinha [1]) are given as particular cases of our results.